DAF-2/insulin-like signaling in C. elegans modifies effects of dietary restriction and nutrient stress on aging, stress and growth. - Wendy B Iser; Catherine A Wolkow (PLoS ONE)
Background Dietary restriction (DR) and reduced insulin/IGF-I-like signaling (IIS) are two regimens that promote longevity in a variety of organisms. Genetic analysis in C. elegans nematodes has shown that DR and IIS couple to distinct cellular signaling pathways. However, it is not known whether these pathways ultimately converge on overlapping or distinct targets to extend lifespan. Principal findings We investigated this question by examining additional effects of DR in wildtype animals and in daf-2 mutants with either moderate or severe IIS deficits. Surprisingly, DR and IIS had opposing effects on these physiological processes. First, DR induced a stress-related change in intestinal vesicle trafficking, termed the FIRE response, which was suppressed in daf-2 mutants. Second, DR did not strongly affect expression of a daf-2- and stress-responsive transcriptional reporter. Finally, DR-related growth impairment was suppressed in daf-2 mutants. Conclusions These findings reveal that an important biological function of DAF-2/IIS is to enhance growth and survival under nutrient-limited conditions. However, we also discovered that levels of DAF-2 pathway activity modified the effects of DR on longevity. Thus, while DR and IIS clearly affect lifespan through independent targets, there may also be some prolongevity targets that are convergently regulated by these pathways.